Acute toxicity study of a polysaccharide based hydrogel from linseed for potential use in drug delivery system - Muhammad Tahir Haseeb; Sajid Bashir; Muhammad Ajaz Hussain; Muhammad Umer Ashraf; Alia Erum; Muhammad Naeem- (Universidade de São Paulo, 2018)
ABSTRACT Linseed hydrogel (LSH) was evaluated by acute toxicity for its potential application in oral drug delivery design. White albino mice and rabbits were divided in four groups (I-IV) and different doses of LSH (1, 2 and 5 g/kg body weight) were given except to the control group (I) that was left untreated. Rabbits were monitored for eye irritation, acute dermal toxicity and primary dermal irritation, whereas, body weight, food and water consumption, hematology and clinical biochemistry, gross necropsy and histopathology of vital organs were scrutinized in mice. LSH was considered safe after eye irritation test as no adverse signs or symptoms were seen in the eye. In dermal toxicity and irritation study, skin of treated rabbits was found normal in color without any edema or erythema. After oral administration, there was no sign of any abnormalities in treated group animals (II-IV). The hematology and clinical biochemistry of treated group animals was comparable with the control group. Histopathology of vital organs has not shown any lesion or abnormalities. In the light of these outcomes, it can be concluded that LSH is not a hazardous biomaterial and could be incorporated as an excipient in oral and dermal preparations.